Actor-Network In The Food Security Program At Class Iia Pancur Batu Prison To Promote The Effectiveness Of The Food Self-Sufficiency Policy - Armada Sinaga, Gabriel; Vanya Simanjuntak, Meitisa (UNIVERSITAS PAKUAN, 2025)
The food security program at the Class IIA Pancur Batu Penitentiary is a national strategic initiative aimed at encouraging inmate independence and supporting food self-sufficiency policies. This study uses the Actor-Network Theory (ANT) framework to identify the human and non-human actors involved and analyze the interconnectedness of the actor network in the program's implementation. The results indicate the formation of a hybrid network involving the Head of the Penitentiary, Head of the Activity Section, inmates, the Directorate General of Corrections, community leaders, the Department of Agriculture, the Prison Cooperative, as well as regulations, land, budget, and seeds. Key obstacles such as limited land and budget were successfully overcome through the role of a third party providing land grants and the Prison Cooperative as operational funding support. Inmates are motivated by premium and remission incentives, and the program's success depends on the solidity of the collaborative network that is able to mobilize resources innovatively. This collaborative model has the potential to be replicated by strengthening formal partnerships and developing a sustainable financial model.